To the mechanism of antibacterial action of colloidal silver: Changes in membrane-associated proton ATPase activity in Escherichia coli and Enterococcus faecalis - D. R. Soghomonyan; N. S. Mnatsakanyan; A. H. Trchounian (ՀՀ ԳԱԱ հրատ.)
It has been shown that colloidal silver (Ag nanoparticles, Ag NPs) significantly inhibited membrane-associated ATPase activity of Escherichia coli ATCC25922 and Enterococcus faecalis ATCC 29212, which was enhanced in the presence of N,N'-dicyclohexylcarbodiimide, inhibitor of the proton F0F1-ATPase. Ցույց է տրվել, որ կոլոիդային արծաթը (Ag նանոմասնիկները) զգալիորեն արգելակում է Escherichia coli ATCC25922-ի և Enterococcus faecalis ATCC 29212-ի թաղանթներին կապակցված ԱԵՖազի ակտիվությունը, որը ուժեղացվել է պրոտոնային F0F1-ԱԵՖազի ապգելակիչ N,N'-երկցիկլոհեքսիլկարբոերկիմիդի առկայությամբ: Было показано, что коллоидное серебро (наночастицы (НЧ Ag) значительно ингибирует мембраносвязанную АТФазную активность Escherichia coli ATCC25922 и Enterococcus faecalis ATCC 29212, которая усиливается в присутствии дициклогексилкарбодиимида ингибитора протонной F0F1-АТФазы.
Keywords: Biology; Biochemistry; Biophysics